“THE INDO-PACIFIC CONCEPT”: GEOPOLITICAL RIVALRY IN THE ASIA-PACIFIC REGION (Academicia Globe: Inderscience Research, 2023)
This article elaborates on the Indo-Pacific concept promoted by the US. Taking into account the importance of the Asia-Pacific region and the actual importance of the region, the competition within the region and the conflict of interests of the leading powers were discussed in detail. The Asia-Pacific region is important not only for the countries of the Far East, but also for the countries of Central Asia and South Asia and a number of other countries. therefore, this region is becoming a competitive field at the global level in recent years.